2012
DOI: 10.2527/jas.2012-5121
|View full text |Cite
|
Sign up to set email alerts
|

A genome scan for QTL affecting resistance to Haemonchus contortus in sheep1

Abstract: Gastrointestinal nematodes are one of the main health issues in sheep breeding. To identify loci affecting the resistance to Haemonchus contortus, a genome scan was carried out using 1,275 Romane × Martinik Black Belly backcross lambs. The entire population was challenged with Haemonchus contortus in 2 consecutive experimental infections, and fecal egg counts (FEC) and packed cell volumes were measured. A subgroup of 332 lambs with extreme FEC was necropsied to determine the total worm burden, length of female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 53 publications
6
66
2
3
Order By: Relevance
“…Moreover, these authors have identified regions on OAR 1 and 12, although these fell below the suggestive threshold. However, strong evidence for a region on OAR 12 affecting FEC was recently reported by Sallé et al (2012); in a study investigating experimentally infected Martinique Black Belly  Romane sheep, a cluster of highly significant SNPs on OAR 12 was associated with FEC. However, in the current study, no significant SNPs for either Nematodirus or Strongyles FEC on OAR 12 were detected with either approach.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, these authors have identified regions on OAR 1 and 12, although these fell below the suggestive threshold. However, strong evidence for a region on OAR 12 affecting FEC was recently reported by Sallé et al (2012); in a study investigating experimentally infected Martinique Black Belly  Romane sheep, a cluster of highly significant SNPs on OAR 12 was associated with FEC. However, in the current study, no significant SNPs for either Nematodirus or Strongyles FEC on OAR 12 were detected with either approach.…”
Section: Discussionmentioning
confidence: 94%
“…More recently, GWA studies using higher density SNP panels have become more common. To our knowledge, however, few studies have been published so far using SNP chip data in sheep (for example, Kemper et al, 2011;Sallé et al, 2012). Comparisons across studies are not easy, given the complexity of the trait and the differences among populations and approaches used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenotype available for the two remaining populations (SAR and MBR) was the 'average animal effect' for Strongyles FEC. A detail description of the animals in the MBR population was given in a study by Sallé et al (2012), and for the SAR population in a study by Sechi et al (2009).…”
Section: Methodsmentioning
confidence: 99%